Formulation development and evaluation of transdermal patch of piroxicam for treating dysmenorrhoea - Nilesh M. Mahajan, Grishma H. Zode, Debarshi Kar Mahapatra, Sonali Thakre, Nitin Dumore, Purushottam S. Gangane (Journal of Applied Pharmaceutical Science, 2018)
Dysmenorrhea (pain with menstruation) affects up to 90% of adolescent and young women. Despite the availability of a variety of effective pharmacological treatments, it is frequently left untreated. Non-steroidal anti-inflammatory drugs (NSAIDs) are the best-established initial therapy for dysmenorrhoea. When NSAIDs are given through the oral route, it causes several side-effects like gastric disturbance, stomach ulcer, nausea, vomiting, etc. Piroxicam is an NSAID utilized for treating dysmenorrhoea in the form of tablet formulation. As mentioned above, it also suffers from similar adverse effects. To overcome those conditions, the transdermal patch of piroxicam can serve as a better alternative to the tablets which serves as the safe alternative over oral route. In the present research, the transdermal patch of piroxicam was fabricated by using sustained release hydrophilic and lipophilic polymers containing permeation enhancer and thoroughly evaluated. The transdermal patches of piroxicam were prepared using the combination of polymers, hydroxypropyl methylcellulose E15, polyvinylpyrrolidone (PVP) K30, and ethyl cellulose in different concentration with sodium lauryl sulfate as the permeation enhancer and polyethylene glycol 400 as the plasticizer was used for the formulation of transdermal drug delivery system which demonstrated sustained release of the drug through the patches. The formulation F1 containing hydrophilic and lipophilic polymers (3:1 ratio) showed the maximum release and permeation of drug for a longer time period up to 12 hours which made it suitable for the development of sustained release patches of piroxicam.
Keywords: Dysmenorrhea, piroxicam, transdermal, patch, NSAID, sustained.